Prediction of crack propagation path in pin loaded lugs using boundary element methods - Xu, Hao (Nanyang Technological University, 2023)
Pin loaded lug joints are used extensively in engineering, especially for aerospace applications. They are used in assemblies to connect major components. As the lug joints are under constant loading, there is high stress concentration at the circumference of the pin holes. Cracks can initiate from these locations of high stress concentration and propagate, which can cause failure of the structure with severe consequences. Therefore, it is important to study the nature of crack initiation and propagation in pin loaded lugs, so that preventative measures can be taken before failure occurs. To do this, stress and fracture analysis are carried out on various lugs under pin loading using the boundary element method (BEM). Stress distribution around the pin hole of straight lugs of varying outer to inner radius ratios and under different loading directions were obtained. Cracks of varying lengths were then added at the locations of highest stress in all the lugs, and the stress intensity factors were determined. The results from testing the straight lugs were compared with that of tapered 30° lugs. Analysis showed that lugs with a smaller pin hole relative to the lug’s outer radius have lower stress concentration factors and stress intensity factors, and hence cracks are less likely to initiate and propagate. This is also true for a tapered 30° lug compared to a straight lug. Loading direction also affect stress concentration factors and stress intensity factors.